Large T1 oligonucleotides of Moloney leukemia virus missing in an env gene recombinant, HIX, are present on an intracellular 21S Moloney viral RNA species. - Faller, D V (1978)
HIX, a recombinant derived from Moloney leukemia virus, has an envelope glycoprotein different from that of the Moloney virus. HIX and Moloney viruses share the majority of the large T1 oligonucleotides derived from their genomes but each possesses a set of distinctive oligonucleotides that lie clustered in corresponding regions in the 3' halves of their oligonucleotide maps. These regions presumably contain envelope glycoprotein coding sequences. The type C viral envelope glycoprotein is believed to be translated from a 21S RNA. Thus, at least part of the region of the Moloney virus genome that is altered relative to HIX was expected to be present on such a species. To test this prediction, we purified an intracellular 21S Moloney viral RNA species and analyzed its large T1 oligonucleotides by two-dimensional polyacrylamide gel electrophoresis. This RNA contains one T1 oligonucleotide that is probably derived from the 5' end of the Moloney virus genome, the Moloney virus T1 oligonucleotides that are missing in HIX, and those that lie to their 3' side on the Moloney virus T1 oligonucleotide map.